2000
DOI: 10.1037/0022-3514.78.5.943
|View full text |Cite
|
Sign up to set email alerts
|

Culture, control, and perception of relationships in the environment.

Abstract: East Asian cognition has been held to be relatively "holistic", that is, attention is paid to the field as a whole. Western cognition, in contrast, has been held to be object-focused and control-oriented. We compared East Asians (mostly Chinese) and Americans on detection of covariation and field dependence. The results showed that (1) Chinese participants reported stronger association between events, were more responsive to differences in covariation, and were more confident about their covariation judgments;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

22
460
2
7

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 602 publications
(491 citation statements)
references
References 49 publications
(75 reference statements)
22
460
2
7
Order By: Relevance
“…It would also be interesting to replicate this study in China. China is well known for its holistic culture (Ji, Peng, & Nisbett, 2000; see also Law, Wang, & Hui, 2010). Given this holistic culture, it can be that employees differentiate less between occupational and organizational commitment, as they are both work related, than in less holistic cultures.…”
Section: Limitations and Research Perspectivementioning
confidence: 99%
“…It would also be interesting to replicate this study in China. China is well known for its holistic culture (Ji, Peng, & Nisbett, 2000; see also Law, Wang, & Hui, 2010). Given this holistic culture, it can be that employees differentiate less between occupational and organizational commitment, as they are both work related, than in less holistic cultures.…”
Section: Limitations and Research Perspectivementioning
confidence: 99%
“…Social processes can extend to a basic perceptual and cognitive level, and research from cultural and social psychology indicated that the mimicker characteristics, such as self-construal, are correlated with the perceptual and cognitive mimicker characteristics (Witkin et al 1979;Witkin & Goodenough 1981;Ji et al 2000). Field dependence, for example, which refers to the phenomenon of perceptually integrating objects in their context, goes together with socially being more attuned to others.…”
Section: Evidence For Social Moderators: Mimicker Characteristicsmentioning
confidence: 99%
“…For example, Westerners tend to explain events in terms that refer primarily or entirely to salient objects (including people), whereas East Asians are more inclined to explain events in terms of contextual factors (3)(4)(5). There also are differences in performance on perceptual judgment and memory tasks (6)(7)(8). For example, Masuda and Nisbett (6) asked participants to report what they saw in underwater scenes.…”
mentioning
confidence: 99%
“…The difference in attending to objects vs. context also was shown in a perceptual judgment task, the Rod and Frame test (7). American and Chinese participants looked down a long box.…”
mentioning
confidence: 99%